PERANCANGAN GAME WORDWALL BERBASIS KOLABORATIF DALAM PEMBELAJARAN MATEMATIKA SMP STUDI MATERI ALJABAR - Leo, Meriani; Handayani, Reny Dewi; Kaluge, Agapitus Hendrikus (Universitas Batanghari Jambi, 2026)
This study aims to design an interactive leraning media based on the Wordwall game integrated with a collaborative approach in junior high school mathematics learning on algebra problems, particulary in substitution, as well as the domaninance of conventional leraning methods that provide limited interaction and collaboration opportunities. The research method used is Research Anda Development (R&D) with the 4D development model, consisting of the Define, Develop, and Disseminate stages. This article focuses on the first two stages, namely Define and Design. The Define stage includes the analysis of teacher and student needs as well as the characteristics of the leraning material, while the Design stage involves the creation of media layout, qustion formats, and game mechanisms using the “Open the Box” feature on Wordwall. The design result in a media product called “Kelas Aljabar”, containing 10-15 multiple-choice questions categorized into conceptual understanding, algebraic operations, and contextual applications. The game is designed for probelm-solving. This design is expected to serve as the basis for furter development and contribute to the creation of engaging, collaborative, and effective mathematics leraning media.